The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/su151713141
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Using Waste Materials in Flexible Pavement Structures Identified by Optimization Design Approach

Primož Jelušič,
Süleyman Gücek,
Bojan Žlender
et al.

Abstract: This paper presents the design of geosynthetic reinforced flexible pavements and their modification by incorporating waste materials into bonded and unbonded layers of the pavement structure. The optimal design of flexible pavements was achieved by minimizing the construction cost of the pavement. The incorporation of waste materials into the pavement structure affects the material properties. Therefore, along with the traffic load, the effects of the material properties of the asphalt concrete, base layer, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Studies showed a significant improvement in the CBR value of the subgrade when 15% fly ash was incorporated into the subgrade layer, reducing the required thickness and lowering the cost of the asphalt pavement structure. Therefore, reducing the fill weight can diminish the tension towards subgrade, as well as prevent excessive settlements on the road [46]. Studies revealed that ashes improved the bearing capacity compared to non-ash road structures, and ash structures are suitable options for the rehabilitation of forest roads and peatlands [11].…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed a significant improvement in the CBR value of the subgrade when 15% fly ash was incorporated into the subgrade layer, reducing the required thickness and lowering the cost of the asphalt pavement structure. Therefore, reducing the fill weight can diminish the tension towards subgrade, as well as prevent excessive settlements on the road [46]. Studies revealed that ashes improved the bearing capacity compared to non-ash road structures, and ash structures are suitable options for the rehabilitation of forest roads and peatlands [11].…”
Section: Discussionmentioning
confidence: 99%